2011
DOI: 10.1165/rcmb.2010-0352oc
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Monoxide Activates Autophagy via Mitochondrial Reactive Oxygen Species Formation

Abstract: Autophagy, an autodigestive process that degrades cellular organelles and protein, plays an important role in maintaining cellular homeostasis during environmental stress. Carbon monoxide (CO), a toxic gas and candidate therapeutic molecule, confers cytoprotection in animal models of acute lung injury. The mechanisms underlying CO-dependent lung cell protection and the role of autophagy in this process remain unclear. Here, we demonstrate that CO exposure time-dependently increased the expression and activatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
109
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(117 citation statements)
references
References 45 publications
7
109
1
Order By: Relevance
“…10 CO increased the expression of LC3B in mouse lung and in cultured human alveolar or human bronchial epithelial cells as well as increased autopha gosome formation in epithelial cells as seen by electron microscopy and green fluorescent protein-LC3 puncta assays. This increase in autophagy activity was inhibited by N-acetyl-l -cysteine and the mitochondriatargeting antioxidant Mito-TEMPO, suggesting that CO promotes the autophagic process through mitochondrial reactive oxygen species (ROS) generation.…”
Section: Autophagy In Acute Lung Injurymentioning
confidence: 84%
See 1 more Smart Citation
“…10 CO increased the expression of LC3B in mouse lung and in cultured human alveolar or human bronchial epithelial cells as well as increased autopha gosome formation in epithelial cells as seen by electron microscopy and green fluorescent protein-LC3 puncta assays. This increase in autophagy activity was inhibited by N-acetyl-l -cysteine and the mitochondriatargeting antioxidant Mito-TEMPO, suggesting that CO promotes the autophagic process through mitochondrial reactive oxygen species (ROS) generation.…”
Section: Autophagy In Acute Lung Injurymentioning
confidence: 84%
“…This increase in autophagy activity was inhibited by N-acetyl-l -cysteine and the mitochondriatargeting antioxidant Mito-TEMPO, suggesting that CO promotes the autophagic process through mitochondrial reactive oxygen species (ROS) generation. 10 The protection afforded by CO against hyperoxiainduced cell death was also compromised on treatment with siRNA against LC3B. These fi ndings suggest that LC3B plays an important role in the cytoprotection afforded by CO through the production of mitochondrial ROS.…”
Section: Autophagy In Acute Lung Injurymentioning
confidence: 90%
“…CO is an endogenous product of heme oxygenase activity that has been shown to exert potent cytoprotection against tissue injury including kidney fibrosis (34), and recently CO has been shown to induce autophagy (48). Lowdose CO (250 ppm) increased the expression and activation of the autophagic protein LC3 in the mouse lung, and in cultured human alveolar (A549) or bronchial epithelial cells in a timedependent manner (48). Our present study also demonstrated that CO induced Beclin 1 and LC3 expression in the mouse kidneys.…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy has recently been implicated in the regulation of hyperoxia-induced epithelial cell death (13). The hallmark of autophagy lies in the conversion of LC3-I activated by ATG7, transferred to ATG3, and conjugated to phosphatidylethanolamine at the outer and inner autophagosomal membrane to form LC3-II (13).…”
Section: Hyperoxia Induces Autophagy In Lung Epithelial Cells and Neomentioning
confidence: 99%
“…The hallmark of autophagy lies in the conversion of LC3-I activated by ATG7, transferred to ATG3, and conjugated to phosphatidylethanolamine at the outer and inner autophagosomal membrane to form LC3-II (13). Although LC3-II increase is considered a standard marker of autophagy activation, it is important to assess the multiple components of the signaling pathway and the autophagic flux (14).…”
Section: Hyperoxia Induces Autophagy In Lung Epithelial Cells and Neomentioning
confidence: 99%